HUBUNGAN BODY IMAGE DENGAN TINGKAT KEPERCAYAAN DIRI PADA SISWI DI MAN PINRANG - Aiman, Aiman; Saleh, Ariyanti; Hastuti, Hastuti; Fitriani, Nurlaila (Alauddin Scientific Journal of Nursing, 2026)
Adolescent girls frequently experience body image concerns that may affect self-confidence and well-being. This study aimed to examine the relationship between body image and self-confidence among female students at MAN Pinrang. A cross-sectional design was used with 222 respondents (aged 16–18 years) selected by simple random sampling. Body image was measured with the MBSRQ-AS (33 items) and self-confidence with the Lauster Self-Confidence Scale (25 items). Data were collected online and analyzed using Spearman’s rho (p=0.05). Most students reported neutral body image (55.9%) followed by less-good (43.2%); only 0.5% were positive or low. Self-confidence was predominantly “sufficient” (75.2%), with 20.7% in the “low” category. A significant, positive, moderate correlation was found between body image and self-confidence (r=0.431, p<0.001, n=222), indicating that more positive body image is associated with higher self-confidence. Findings suggest the need for school-based health promotion integrating body-positivity education, media-literacy, and supportive counseling led by school nurses and counselors to strengthen students’ self-acceptance and social functioning